A Plastid-Bound Ankyrin Repeat Protein Controls Gametophyte and Early Embryo Development in Arabidopsis thaliana - Kulichová, Katarína; Pieters, Janto; Kumar, Vinod; Honys, David; Hafidh, Said (Frontiers in Plant Science, 2022)
Proplastids are essential precursors for multi-fate plastid biogenesis, including chloroplast differentiation, a powerhouse for photosynthesis in plants. Arabidopsis ankyrin repeat protein (AKRP, AT5G66055) is a plastid-localized protein with a putative function in plastid differentiation and morphogenesis. Loss of function of akrp leads to embryo developmental arrest. Whether AKRP is critical pre-fertilization has remained unresolved. Here, using reverse genetics, we report a new allele, akrp-3, that exhibited a reduced frequency of mutant embryos (<13%) compared to previously reported alleles. akrp-3 affected both male and female gametophytes resulting in reduced viability, incompetence in pollen tube attraction, altered gametic cell fate, and embryo arrest that were depleted of chlorophyll. AKRP is widely expressed, and the AKRP-GFP fusion localized to plastids of both gametophytes, in isolated chloroplast and co-localized with a plastid marker in pollen and pollen tubes. Cell-type-specific complementation of akrp-3 hinted at the developmental timing at which AKRP might play an essential role. Our findings provide a plausible insight into the crucial role of AKRP in the differentiation of both gametophytes and coupling embryo development with chlorophyll synthesis.